Serial Picture Media: A Strategy to Optimize Logical Thinking Ability in Children Aged 5–6 Years - Tutus Nika Hardiyanti; Iys Nur Handayani (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the low logical thinking ability of children aged 5–6 years, as indicated by their limitations in classifying, sequencing, and comparing. The study aimed to improve children’s logical thinking ability through the use of serial picture media. This research is a classroom action research conducted at TK Pertiwi Sri Hastuti Simbang with 32 children as subjects. The research was carried out in two cycles with four meetings, which included the stages of planning, implementation, observation, and reflection. The pre-research results showed that the logical thinking ability of children aged 5–6 years was still dominated by the categories of Not Yet Developed (BB) and Beginning to Develop (MB). After the intervention in Cycle I, children’s logical thinking ability increased with an average achievement of 56.24%. A more significant improvement occurred in Cycle II, where the average achievement of children’s logical thinking ability reached 81.25%. The results of this study indicate that the use of serial picture media can improve the logical thinking ability of children aged 5–6 years.